A comparative study on damage assessment of tubular members subjected to mass impact. (March 2016) - Cerik, Burak Can; Shin, Hyun Kyoung; Cho, Sang-Rai
Abstract: This paper focuses on the behaviour of tubular members when subjected to low-velocity mass impact. Particular emphasis is given to the numerical assessment of impact damage and the classification of impact response of tubular members. Damage extents of 12 tubular frame test models were predicted and used for quantifying the modelling uncertainties of the numerical tools. USFOS and ABAQUS software packages were used with beam and shell elements, respectively. Based on the test results and the parametric studies performed, the influence of the geometrical parameters and the interaction between the local shell denting and the global beam deformation modes are discussed. A classification of the impact response of the tubular members based on their relative resistance against shell denting and beam plastic collapse load is proposed. Finally, existing analytical models for each energy dissipation mode are visited and modifications are proposed. Highlights: Modelling uncertainties for numerical tools used in damage assessment of tubular members are assessed. Classification of impact response of tubular members is proposed. Applicability of simplified methods for impact response assessment of tubular members is set on the proposed classification.